Risk factors and clinical presentations of long COVID in Africa: A scoping review - Enos Moyo; Munashe Chimene; Perseverance Moyo; Godfrey Musuka; Derek Mangoya; Grant Murewanhema; Tafadzwa Dzinamarira (Elsevier, 2023)
COVID-19-related complications can last for years, even in patients who are asymptomatic during the acute phase, a phenomenon referred to as long COVID. This scoping review aimed to summarize the risk factors and clinical symptoms of long COVID in Africa between 2020 and 2022. Five studies were included. Three of the studies used in this review were retrospective cross-sectional studies, one was a prospective cohort study while another one was a case-control study. The review identified several risk factors for long COVID, including being female, being older than 40 years, having more than four acute COVID-19 symptoms, and having concomitant conditions such as asthma, hypertension, and depression. General, respiratory, cardiovascular, otolaryngological, gastrointestinal, and neurological symptoms were among the reported long COVID symptoms. To ensure that patients with long COVID are diagnosed and treated early, the risk factors and clinical symptoms of long COVID need to be identified for different population groups.